2015
DOI: 10.1016/j.juro.2014.10.049
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Controlled Trial Evaluating the Effectiveness of Group vs Individual Urotherapy in Decreasing Symptoms Associated with Bladder-Bowel Dysfunction

Abstract: Urotherapy, regardless of modality, effectively improved bladder-bowel dysfunction symptoms. A definitive randomized controlled trial is feasible, considering that a high recruitment rate (76%) for this population has been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…urge incontinence and frequency) and voiding symptoms. Biofeedback therapy: This is indicated for children aged ≥5 years. Devices are used to provide visual, tactile and other sensory information to help patients understand the contraction of the pelvic floor muscles, and such understanding will be used to improve lower urinary tract function. Treatment of defecation problems: Correction of fluid intake, dietary intervention and use of laxatives. Urotherapy: Comprehensive conservative therapy by specialists is necessary, including: (i) good understanding of the anatomy and physiology of the lower urinary tract; (ii) advising patients on how to alleviate lower urinary tract dysfunction (e.g. appropriate urination posture, regular urination and not holding urine); (iii) advice on lifestyle (e.g.…”
Section: Capmentioning
confidence: 99%
“…urge incontinence and frequency) and voiding symptoms. Biofeedback therapy: This is indicated for children aged ≥5 years. Devices are used to provide visual, tactile and other sensory information to help patients understand the contraction of the pelvic floor muscles, and such understanding will be used to improve lower urinary tract function. Treatment of defecation problems: Correction of fluid intake, dietary intervention and use of laxatives. Urotherapy: Comprehensive conservative therapy by specialists is necessary, including: (i) good understanding of the anatomy and physiology of the lower urinary tract; (ii) advising patients on how to alleviate lower urinary tract dysfunction (e.g. appropriate urination posture, regular urination and not holding urine); (iii) advice on lifestyle (e.g.…”
Section: Capmentioning
confidence: 99%
“…A recent pilot study was also published about the efficacy of group visits for urotherapy which have been proposed to improve compliance and decrease the costs of care. The study was focused on older children (>5 years of age) with BBD and showed significant improvement in LUT symptoms in children receiving either individual or group therapy sessions [44]. …”
Section: Bowel and Bladder Dysfunctionmentioning
confidence: 99%
“…Certainly, CE trials are favoured by medical staff and parents when seeking consent [45]. Despite a number of widely accepted therapies [19] there is insufficient evidence to support such a comparative treatment for NE in children. For this reason, placebo-control is still appropriate for a non-life threatening condition such as NE [44] yet concerns about their child being randomized to ineffective treatments may outweigh the benefits for some parents [45].…”
Section: Discussionmentioning
confidence: 99%
“…The most common strategies utilised are waking the child during the night to use the bathroom and limiting the child’s water intake before going to bed [18]. Behavioural or educational therapies for NE such as urotherapy or bladder retraining are widely accepted and considered as a mainstream treatment option for non-neurogenic lower urinary tract dysfunction in children [19] with the aim to normalise bladder emptying and storage by teaching relaxed voiding techniques [20]. Alarm interventions have demonstrated moderate effectiveness in reducing NE in approximately two thirds of children with relapse occurring in half children with ceasing the treatment [21].…”
Section: Introductionmentioning
confidence: 99%